Electrode Based on the MWCNTs and Electropolymerized Thymolphthalein for the Voltammetric Determination of Total Isopropylmethylphenols in Spices - Natalia Chernousova; Guzel Ziyatdinova (Micromachines, 2023)
Isopropylmethylphenols, namely thymol and carvacrol, are natural phenolic monoterpenoids with a wide spectrum of bioactivity making them applicable in the cosmetic, pharmaceutical, and food industry. The dose-dependent antioxidant properties of isopropylmethylphenols require their quantification in real samples. Glassy carbon electrode (GCE) modified with multi-walled carbon nanotubes (MWCNTs) and electropolymerized thymolphthalein has been developed for the sensitive quantification of isopropylmethylphenols. Conditions of thymolphthalein electropolymerization (monomer concentration, number of cycles, and electrolysis parameters) providing the best response to thymol have been found. Scanning electron microscopy and electrochemical methods confirm the effectivity of the electrode developed. The linear dynamic ranges of 0.050–25 and 25–100 µM for thymol and 0.10–10 and 10–100 µM for carvacrol with detection limits of 0.037 and 0.063 µM, respectively, have been achieved in differential pulse mode in Britton–Robinson buffer pH 2.0. The selectivity of the isopropylmethylphenols response in the presence of typical interferences (inorganic ions, saccharides, ascorbic acid) and other phenolics (caffeic, chlorogenic, gallic and rosmarinic acids, and quercetin) is a significant advantage over other electrochemical methods. The electrode has been used in the analysis of oregano and thyme spices. Total isopropylmethylphenols contents have been evaluated after a single sonication-assisted extraction with methanol.